Mitigation of an open shaft at a legacy mine site in British Columbia, Canada using polyurethane foam - Sandve, L; Forkheim, E; Slater, M; Bonin, G (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Legacy underground mining sites may include the presence of unsecured openings to surface, such as shafts, vent raises, and portals that pose a risk to public and animal safety. This paper presents a case study of the design methodology and use of a polyurethane foam (PUF) plug for the mitigation of an open shaft at a legacy mine site in British Columbia, Canada. Common methods of securing openings to surface include the design and construction of concrete caps or plugs, installation of steel grates, and/or placement of backfill. The method chosen depends on the remediation objectives, desired lifespan, and project setting. Openings in remote locations may require special considerations to optimise cost and reduce impacts on the environment due to the increased difficulty in transporting equipment and materials to the project site. The shaft that is the subject of this paper had previously been backfilled several times with rockfill by the site Owner, but the backfill had either migrated and/or settled over time, eventually resulting in an expression of surface subsidence. The shaft location is within steep terrain and only accessible from an unsanctioned foot and bike trail which limits access with mobile equipment. The use of PUF was advantageous in this situation due to its portability and ability to be hand-mixed and hand-poured into the opening, reducing the need to transport equipment to the project site which would have impacted the surrounding forest terrain. The PUF plug was constructed to prevent further subsidence and seal off access to the shaft to provide a long-term mitigative solution. The plug was required to have sufficient density, strength, and thickness to resist anticipated natural loads, and was designed to incorporate cementitious grout and backfill layers to provide ultraviolet (UV) and fire protection, respectively. An inspection port was also included in the design to facilitate long-term performance monitoring. Technical specifications and a work methodology for mitigating the open shaft with PUF were developed to meet the design basis. A quality assurance program consisting of on-site observations and monitoring of site conditions, as well as sampling of the PUF material for third-party density and strength testing was also carried out. A post-construction monitoring program will be implemented beginning in summer 2023, following snow melt, and will consist of visual monitoring at surface and at depth through the installed inspection port.
Keywords: mitigation